CREATING FAMILIAL SETTING TO IMPROVE ENGLISH CLASS AUTONOMY - Titik Wahyuningsih (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2016)
This paper is a report of self-evaluation on teaching the students of Teacher Training and Education Faculty, University of Muhammadiyah Purwokerto at Teaching English to Young Learners (TEYL) classes since 2012 until today. Research and Development design is used here to test the feasible method to improve the endeavors of the classes.Four different classes at even semesters are analyzed as the data: TEYL class A 2012/2013 (28 students), TEYL class B 2012/ 2013 (28 students), TEYL class 2013/2014 (36 students), and TEYL class 2014/2015 (52 students). The students of 2012/2013 were asked to find the characteristics of children’s learning styles topic as individual task while students of 2013/2014 and 2014/2015 were asked to do in group. The groups of the last two classes were formed in familial setting in which the lecturer prepared cards with 4 different surnames. Those got the same surname became one group and they became a big family in which they pretend to be brothers and sisters of different ages. Each, then, became one responsible most to find out characteristics of his supposed age. The discovery shows that the classes of 2012/2013 tended to be inactive as they wished they have got information from their friends while what we call now the members of the families of 2013/ 2014 and 2014/2015 showed great responds. Almost all of the members of the family showed their enthusiasm, collaborative works, as well as understanding. Keywords: familial setting, autonomy